Fetal cardiology simplified a practical manual - Sharland, G. K. (Gurleen K.) (Tfm Pub. Ltd., 2013)
Foetal cardiology has developed dramatically into a subspecialty. This book is designed as a practical guide for those performing foetal heart scans, but without the expertise of a foetal cardiologist. It helps the user to recognise the common forms of foetal cardiac abnormality and to appreciate the associated lesions and outcome